False Dawn: The Delusions of Global Capitalism by John Gray. London: Cranta Publications, 1998. 234 pp. (American Journal of Islam and Society, 1998)
The natural counterpart of a free market economy is a politics of insecurity.If 'capitalism' means 'the free market,' then no view is moredeluded than the belief that the future lies with 'democratic capitalism'.... the free market cannot last in an age in which economic securityfor the majority of people is being reduced by the world economy... a reform of the world economy is needed that accepts a diversity ofcultures, regimes and market economies as a permanent reality.